2018
DOI: 10.1002/jso.25330
|View full text |Cite
|
Sign up to set email alerts
|

Management of local or regional non‐nodal disease

Abstract: Some melanomas develop a striking avidity for lymphatic spread. In spite of multiple recurrences, patients can remain years without visceral metastasis. There is clearly a biologic reason for this lymphotrophic pattern of growth and dissemination, which we have yet to uncover. In-transit metastases have widely diverse clinical presentations and can be a stubborn disease to cure. As a result, a host of treatments exist that should be tailored to the individual patient. K E Y W O R D S diphenylcyclopropenone, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…In our database, ITM is defined as a lesion occurring more than 5 cm from the primary lesion instead of the 2 cm used in the staging manual. 22 In conclusion, this study showed that SNB can be performed for patients experiencing LR or ITM with a high identification rate, although the false-negative rate was considerable (27%). A tumor-positive SN was found in 13% of the patients and was associated with more recurrences and a worse overall survival rate.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In our database, ITM is defined as a lesion occurring more than 5 cm from the primary lesion instead of the 2 cm used in the staging manual. 22 In conclusion, this study showed that SNB can be performed for patients experiencing LR or ITM with a high identification rate, although the false-negative rate was considerable (27%). A tumor-positive SN was found in 13% of the patients and was associated with more recurrences and a worse overall survival rate.…”
Section: Discussionmentioning
confidence: 60%
“…For unknown reasons, some melanomas predominantly metastasize through lymphatics. 22 Read et al 5 reported that disease was limited to ITMs without distant metastases in 36% of the 190 patients with ITM as the first site of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…However, research has shown that even then, only 19% of patients remain without evidence of recurrence, within a median follow-up of 40 months. 45 Other treatment options, including electrochemotherapy, are thus used in cases of a higher number of skin lesions. New systemic therapies are promising; nonetheless, due to the high cost, as well as to the treatment-related adverse events, it is still advised to treat skin lesions locally, for as long as possible.…”
Section: Discussionmentioning
confidence: 99%
“…4 Many locoregional treatment options exist with varying local control rates and few offering durable improvements in overall survival. 5 Evaluating the efficacy of contemporary systemic therapy compared with the efficacy of locoregional interventions has been a challenge secondary to systemic therapy trials excluding patients with ITM or not reporting them separately as well as the inherent limitations of cross-study comparisons.…”
Section: Introductionmentioning
confidence: 99%